Implementasi kurikulum Merdeka dalam meningkatkan self regulated learning siswa kelas viii di madrasah tsanawiyah Nurul Hidayah Sungai Salak Kecamatan Tempuling - Hatni, Hatni; Syaifuddin, M.; Afriza, Afriza (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in enhancing students’ Self-Regulated Learning (SRL) at MTs Nurul Hidayah Sungai Salak. The research employed a qualitative approach, with data collected through observation, in-depth interviews, and document analysis. The research subjects included the school principal, the vice principal of curriculum, and ten eighth-grade students. The findings indicate that the Merdeka Curriculum has been effectively implemented in promoting the development of students’ SRL abilities, such as goal setting, self-reflection, time management, and initiating help-seeking when facing difficulties. Students were also able to apply appropriate learning strategies and demonstrated intrinsic motivation as well as perseverance in addressing academic challenges. Furthermore, the school provides systematic support that strengthens students’ learning autonomy. Therefore, the Merdeka Curriculum contributes significantly to shaping students into independent learners in accordance with the goals of 21st-century education.